DERADIKALISASI ATAS PEMAHAMAN AL-QUR’AN (ANALISIS SEMANTIK DAN KONTEKS HISTORIS TERHADAP AYAT-AYAT TENTANG JIHĀD DAN QITĀL) - Tahir, Muhammad Suaib (LP2M Universitas PTIQ Jakarta, 2023)
A mistake in understanding these verses about jihād and qitāl can trigger the emergence of various radical ideas. Someone with radical views only understands these verses textually, so he will assume that all non-Muslims must be fought. One of the efforts to deradicalize such an understanding is to study and analyze the verses of jihad and qital with semantic analysis and historical context. Semantic analysis is used to analyze variations and contexts of word meanings from key words in the Qur'an. The keywords analyzed in this study are the terms